CONSCIENTIZATION THROUGH THE CONTEXT OF A BOOK CLUB: ADULTS’ EXPERIENCES OF CONSCIOUSNESS-RAISING - Rachel M Cassity (Adult Education Research Conference, 2016)
The purpose of this qualitative study is to understand the lived experiences of consciousness-raising for adults through the context of book clubs. Research about adult participation in book clubs remains scarce. Therefore, this study seeks to highlight how these contexts might promote adult learning and Conscientization.
Keywords: Book clubs; adult learning; Conscientization